Delayed Positive Feedback Can Stabilize Oscillatory Systems - Abdallah, C.; Dorato, P.; Benites-Read, J.; Byrne, R. (American Control Conference, 1993, 1993)
This paper expands on a method proposed in [1] for stabilizing oscillatory system with positive, delayed feedback. The closed-loop system obtained is shown (using the Nyquist criterion) to be stable for a range of delays.